ASSERTIVE TRAINING TO IMPROVE PUBLIC SPEAKING SKILLS OF STUDENTS WITH INTELLECTUAL DISABILITIES: A QUALITATIVE CASE STUDY IN A SPECIAL SCHOOL - Syaiful Arifin; Dewi Masyitoh (CV. TOTUS TUUS, 2026)
Students with intellectual disabilities often experience severe difficulties in public speaking, including low verbal output, limited language organization, and low self-confidence when speaking in front of others. This study aimed to describe students’ initial public speaking abilities, to portray the implementation of assertive training, and to analyze its influence on improving public speaking skills among students with mild intellectual disabilities at SLB Lentera Hati Pesanggaran. A qualitative descriptive case-study design was employed. Participants were selected purposively, and data were collected through participatory observation, in-depth interviews with students, teachers, and parents, as well as documentation. Data were analyzed using Miles and Huberman’s interactive model (data reduction, data display, and conclusion drawing) with source and method triangulation to ensure trustworthiness. Results indicated that, prior to the intervention, students spoke in very low volume, produced fragmented sentences, avoided eye contact, and were reluctant to answer questions. After 6–8 sessions of structured assertive training—covering relaxation, modeling, role play, guided practice, and in vivo exercises—students showed noticeable improvements in voice audibility, clarity and length of utterances, eye contact, and willingness to respond in class. The study concludes that assertive training is a promising strategy to foster public speaking skills and self-confidence among students with intellectual disabilities. The findings imply that assertive training can be integrated into counseling services and classroom routines in special schools. Future research is recommended to involve larger samples, longer follow-up periods, and mixed-method or quasi-experimental designs to strengthen causal inferences and explore broader socio-emotional outcomes.